A "holistic" sonographic view on congenital heart disease: How automatic reconstruction using fetal intelligent navigation echocardiography eases unveiling of abnormal cardiac anatomy part II—Left heart anomalies. Issue 5 (29th March 2021) - Weichert, Jan; Weichert, Alexander
Abstract: Volume ultrasound has been shown to provide valid complementary information on fetal anatomy. Four‐dimensional assessment (4D) of the fetal cardiovascular system using spatial–temporal image correlation (STIC) allows for detailed examination of a highly complex organ from the early second trimester onward. There is compelling evidence that this technique harbors quite a number of diagnostic opportunities, but manual navigation through STIC volume datasets is highly operator dependent. In fact, STIC is not incorporated yet into daily practice. Application of the novel fetal intelligent navigation echocardiography (FINE) considerably simplifies fetal cardiac volumetric examinations. This automatic technique applied on cardiac volume datasets reportedly has both high sensitivity and specificity for the detection of congenital heart defects (CHDs). Part I reviewed current data regarding detection rates of CHDs and illustrated the additional value of an automatic approach in delineating cardiac anatomy exemplified by congenital lesions of the right heart. In part II of this pictorial essay, we focused on left heart anomalies and aimed to tabulate recent findings on the quantification of normal and abnormal cardiac anatomy.